Strategic Analysis and Competitive Advantage Strategies for A Leading Information Security Enterprise: A Case Study of Q Technology Company - Liyuan, Qiu; Ruanggoon, Jirapong; Wana, Chayoot (Science, Technology, and Social Sciences Procedia, 2024)
This research aimed to 1) Analyze the competitive environment of Q Technology Company and 2) Utilize the Quantitative Strategic Planning Matrix (QSPM) to formulate competitive advantage strategies for Q Technology Company. To conduct a comprehensive analysis, document studies, a questionnaire survey involving 40 information security practitioners, and 7 expert interviews were utilized. The study investigated both the external and internal environments. Subsequently, key factors affecting the company were identified, followed by external factor evaluation (EFE) and internal factor evaluation (IFE) to assess the company’s situation. QSPM analysis was then employed to determine Q Technology Company’s strategies. The research findings revealed that 1) Q Technology Company faced a promising landscape with supportive policies and expanding market demand. Despite challenges like market competition and technological advancements, the company boasted strengths in brand influence and customer base. However, it needed to address weaknesses such as the lack of core technology and weak profitability. By leveraging its strengths, the company could penetrate international markets and enhance profitability through improved services and technology development. 2) Q Technology Company’s competitive advantage strategies were formulated through a SWOT analysis, resulting in SO, ST, WO, and WT alternatives. The QSPM analysis favored the ST strategy, leveraging the company’s strengths to address external threats. By collaborating with promising enterprises, focusing on customized services for its broad customer base, and expanding internationally, Q Company aimed to sustain growth and competitiveness in the cybersecurity market.